PERAN AGAMA KRISTEN DALAM MEMBETUK IDENTITAS DAN NILAI-NILAI MORAL INDIVIDU - Sipora Franzetsa Ndun (CV. Adiba Aisha Amira, 2025)
The Christian faith plays a vital role in shaping individual identity and moral values. In daily life, Christian teachings such as love, forgiveness, justice, and humility serve as foundational principles that influence a person's way of thinking, behaving, and interacting with others. An individual’s identity is not solely shaped by cultural and social backgrounds but also by spiritual values instilled through early religious education and participation in faith communities. Through practices like worship, Bible reading, and fellowship within the church, individuals are guided to understand their identity as valuable creations of God. In the midst of modern challenges that often blur moral boundaries, the role of Christianity becomes increasingly essential as a guiding force that provides direction and purpose. Therefore, the development of a strong identity and character cannot be separated from the active and relevant presence of faith in a person's life. This study explores how Christian teachings help form personal identity and embed moral values as a compass for navigating social realities.